Platelet to Lymphocyte Ratio Predicts Contrast-Induced Nephropathy in Patients With ST-Segment Elevation Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention. (January 2018) - Sun, Xi-peng; Li, Jing; Zhu, Wei-wei; Li, Dong-bao; Chen, Hui; Li, Hong-wei; Chen, Wen-ming; Hua, Qi
We investigated the relationship between platelet to lymphocyte ratio (PLR) and contrast-induced nephropathy (CIN) in patients with ST-segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (pPCI). We enrolled 5719 patients in 3 tertiary hospitals from January 2005 to December 2010. The PLR was calculated as the ratio of platelet to lymphocyte counts on admission. Serum creatinine level was measured before and within 72 hours after contrast medium administration. To evaluate the relation between PLR and CIN, the 5719 patients were divided into a CIN group and a non-CIN group. Contrast-induced nephropathy occurred in 252 (4.4%) patients. Patients in the CIN group had significantly higher PLR than those in the non-CIN group (173.8 [62.3] and 116.2 [51.7], respectively; P < .001). In logistic regression analysis, PLR was an independent predictor of CIN (odds ratio: 1.432, 95% confidence interval: 1.205-1.816, P = .031), along with age, diabetes mellitus, creatinine, estimated glomerular filtration rate, and neutrophil to lymphocyte ratio. In conclusion, a higher PLR was an independent risk factor for the development of CIN in patients with STEMI undergoing pPCI.